Eutropis Carinata (Common Skink), Eutropis Macularia (Rock Skink). Endoparasites - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2009)
Eutropis carinata, a terrestrial, diurnal skink, occurs in a wide variety of habitats in Sri Lanka, India, Bangladesh, and Nepal (Das and De Silva 2005. A Photographic Guide to Snakes and Other Reptiles of Sri Lanka. Ralph Curtis Publ., Sanibel Island, Florida. 144 pp.). Eutropis macularia, a semi-fossorial skink, occurs in Sri Lanka, India, Pakistan, Nepal, Bangladesh, Bhutan, east to mainland southeast Asia (Das and de Silva, op. cit.). There are, to our knowledge, no published records of helminths from these species. The purpose of this note is to establish the initial helminth lists for E. carinata and E. macularia.